The Preparation of Tetramethyl 1,1′,3,3′-Ruthenocenetetracarboxylate and Tetramethyl 1,1′,3,3′-Osmocenetetracarboxylate, and a Simplified Synthesis for Tetramethyl 1,1′,3,3′-Ferrocenetetracarboxylate - Hein, Julia; Klett, Jan (Synthesis, 2019)
Substituted metallocenes with more than two substituents have to be synthesized using doubly substituted cyclopentadiene rings in a reaction with a metal compound or by the introduction of additional functional groups to an already di-substituted metallocene. The direct formation of tetra-substituted metallocenes often suffers due to insufficient reactivity of the reagents or the resulting product mixtures, which are hard to separate. In this work, a protocol, which was successful in a tetra-substitution of ferrocene by a tetra-metalation followed by a reaction with carbon dioxide, is used to perform the tetra-substitution of ruthenocene and osmocene. In addition, a simplified protocol for the tetra-functionalization of ferrocene using commercially available components on a medium scale is described.
Keywords: metallocene; deprotometalation; ruthenocene; osmocene; alkali metal; superbase